All Days 2015
DOI: 10.2118/174489-ms
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Additives and Foam to Enhance SAGD Performance

Abstract: Adding chemical additives with in-situ generation of foam is an approach to enhance SAGD (steam assisted gravity drainage) performance both in terms of oil production and SOR (steam oil ratio). Simulation study tells that, owing to gas mobility control, interfacial tension reduction and emulsification, the steam chamber profile is substantially controlled with a reduced heat loss, and the residual oil saturation drops dramatically. A heterogeneous model based on a Suncor Firebag project is further employed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 67 publications
0
3
0
1
Order By: Relevance
“…加拿大Athabasca地区在1988年也曾 经进行蒸汽泡沫驱现场试验, 试验中表面活性剂的注 入速度为500~1400 L/d, 最终产油上升30% [69] . Fried-mann等人 [70] 图 2 剩余油饱和度分布图 [73] . (a) 常规SAGD; (b) SAGD-化学泡沫复合驱…”
Section: 黏度在50℃下为2×10unclassified
“…加拿大Athabasca地区在1988年也曾 经进行蒸汽泡沫驱现场试验, 试验中表面活性剂的注 入速度为500~1400 L/d, 最终产油上升30% [69] . Fried-mann等人 [70] 图 2 剩余油饱和度分布图 [73] . (a) 常规SAGD; (b) SAGD-化学泡沫复合驱…”
Section: 黏度在50℃下为2×10unclassified
“…In addition, interlayer can also have an impact on SAGD production, Dou and Li carried out a thermal recovery physical simulation experiment to study the influence of interlayer on steam cham-ber, and the result showed that the steam chamber was forced to develop laterally along the interlayer [33]. Meanwhile, in order to enhance SAGD recovery, multiple media-assisted SAGD technologies such as expanding solvent-SAGD, noncondensate gas-assisted SAGD (CO 2 , N 2 , flue gas, and natural gas), and foam-assisted SAGD have been proposed [34][35][36][37]. These techniques decreased the steam consumption and steam heat loss; the development of steam chamber is promoted.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, foam generation causes some portion of the injected gas to be transferred to the reservoir areas that is not swept previously. This improves the sweep efficiency in the reservoir. ,,, Also, the efficiency of steam-assisted gravity drainage (SAGD) method can be improved with contribution of foam. , …”
Section: Introductionmentioning
confidence: 99%